The Lion's Masquerade : A Sequel to The Peacock at Home - Dorset, Catherine Ann Turner, 1750?-1817? (Salt Lake City, UT : Project Gutenberg, 2010)
"The Lion's Masquerade" by Catherine Ann Turner Dorset is a whimsical narrative poem written in the early 19th century. This enchanting work serves as a sequel to "The Peacock at Home" and can be categorized as a children's literature piece. The book's probable topic revolves around a grand masquerade ball hosted by the Lion, featuring various animal characters who embody different traits and virtues reflective of society. In the story, the Lion, envious of the social success of the Peacock's recent ball, decides to host his own grand masquerade to reaffirm his status as king of the beasts. The animals in the forest prepare for the event with excitement and creativity, selecting costumes that reflect their personalities. The masquerade brings a colorful array of guests, from the gluttonous Baboon to the wise Elephant, highlighting their characteristics through their chosen outfits. The Lion delivers a speech at the banquet, urging his guests to lay aside their negative traits and celebrate in harmony, echoing themes of unity and civility. Ultimately, the festivities promote a sense of community among the attendees, suggesting an underlying moral lesson about behavior and social interactions. (This is an automatically generated summary.)
Release date is 2010-04-30
E-text prepared by David Wilson and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Children's poetry; Animals -- Juvenile poetry